The risk of being a drug-dealer: the involvement of university students in the retail drug-dealing of marijuana in Lima Metropolitana - Pastor Armas, Alvaro (2016)
The article analyzes the involvement of seven university students in drug dealing in Metropolitan Lima. This qualitative study based its analysis on semi-structured interviews and seven-month fieldwork.The article evidences that the experience as recreational drug users allows them to grasp basic routines related to the market: who, where and how to buy drugs. Based on that previous experience, students get involved in marijuana exchanges because: (i) they want to sell it in order to smoke for free; (ii) they have a good connection with and become a broker for their friends, or (iii) they are interested in generating extra-money to maintain a lifestyle associated with recreational consumption in middle-class university contexts (going to parties, going on trips, buying other drugs, among others).Subsequently, students emphasize their interest in generating monetary incomes and begin to sell marijuana more frequently and in greater quantities. This escalation does not lead to the development of and identity as a ‘drug-dealer’, nor an involvement in other criminal activities.